TAXONOMIC COMPOSITION AND POPULATION LEVEL OF THE PROSTHETIC BED MUCOSA MICROBIOTA AT THE DENTAL ARCH DEFECTS IN PATIENTS MADE PROSTHETIC APPLIANCE WITH PARTIAL DENTURE - Ozhogan, Z.R.; Yasinskyi, M.M.; Levandovskyi, R.A.; Bulyk, R.Y. (World of Medicine and Biology, 2019)
The article considers the taxonomic composition and the population level of the oral cavity mucous membrane microbiota and changes in their characteristics, after dental prosthetic rehabilitation with partial dentures. In patients with partial loss of teeth, made a prosthetic appliance for the teeth with conventional removable dentures, the taxonomic composition of microbiota changes in the gum mucosa due to the biotope contamination with opportunistic S. aureus and yeast-like fungi of the Candida genus, S. haemolyticus, K. pneumoniae, enterobacteria (E.coli , K.pneumoniae, E.cloacae), B.catarralis, M.lacunata and due to partial elimination of S. sialivarius, S.sanguis, S. mutans, S. mitis from the biotom. In 78.72% of patients, microorganisms isolated and identified from the surface of the prosthetic bed, are in associations that consist of 2 (31.70% cases), 3 (8.51%) and 4 (8.51 %) taxons. The most numerous associations consisting of 2 taxons were: S. aureus and M. lacunata; S. aureus and N. flavescens; S. haemolyticus and B.catarrhalis as well as C. albicans and S. epidermidis. In the biotope (surface of the prosthetic bed gums mucous membrane), these patients made a prosthetic appliance for the teeth with partial removable plate dentures, the population level is reduced in S. salivarius, S. sanguis, S. mutans, S. mitis and significantly increases in opportunistic staphylococci (S. aureus, S. haemolyties, S. epidermidis), S. pyogenes, enterobacteria (E. coli, K. pneumoniae, E. clocacae), B.catarrhalis. Microorganisms (S. aureus and C. albicans) reach a high population level, and it also grows in S. haemoliticus, S. epidermidis, S. pyogenes, E. coli, E. cloacae, K. pneumoniae.
Keywords: partial removable dentures; taxonomic composition; population level